Impact of changes in climatic elements on crop yield in Kwara State: a comparative analysis between grains and root tubers - Tunde, A.M. (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study presents a comparative analysis on the effects of climatic variations on crop yield in Kwara State using grains and root tubers. Annual climatic and crop yield data for a period of twenty years (1998-2017) were collected from Kwara State Agricultural Development Project. Climatic data obtained includes rainfall, number of rainy days, relative humidity, maximum and minimum temperature. Grain crops and root tubers’ data include maize, sorghum, rice, millet, cowpea, soya beans and cassava, yam, sweet potato respectively. These were however subjected to trend, correlation and multiple regression analyses. The results obtained revealed that changes in climatic elements have impact on both grains and root tubers’ yield although low but in combination with other factors such as edaphic, farm techniques and seed varieties among others. The regression result revealed that the variance in maize, sorghum, rice, millet, cowpea and soya beans respectively be explained by the climatic elements under study. Similarly, of the variance in cassava, yam, and sweet potato respectively can also be explained by the climatic elements under study. Hence, there is no significant difference in impacts of changes in climatic elements between grains and root tuber. Therefore, it can be concluded that the changes in climatic elements can be seen as part of the factors responsible for low agricultural yield and production in the state and country at large. Policies that will improve the status of agricultural yield and production should therefore, be embarked upon.